PERANCANGAN DETEKSI LONGSOR DI BUKIT WATU BUCENG DUSUN KETOS DESA WONODADI KULON - Ahmad Ridho’i; Sunu Priyawan; Bantot Sutriono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
At the current state of nature that terexploitasi resulting in damage them in mountainous areas prone to landslides and flooding, it requires the existence of early warning against the dangers that threaten and cause substantial losses to society. Landslide is sometimes difficult to detect, ground movement can not always be monitored because it requires the development of an early warning system landslides that can provide early warning of distance. Design and manufacture of early warning against the danger of landslides is necessary, for the detection system landslide hazard consisting of a sensor monitoring the movement of land, processor (microcontroller), and modem sabagai sender sms (short message service) to the mobile number designated or interested provide guidance to the people affected in the landslide.Keywords: landslide detection, microcontroller, modem